Guangxi 2010: Six new cave fern species of Polystichum (Dryopteridaceae) - He, Hai; Zhang, Li-Bing (Phytotaxa, 2026)
Six new species of cave ferns of Polystichum are described and illustrated from southern China’s Guangxi Zhuang Autonomous Region based on materials collected in 2010. These six new species include P. atroviridis, P. bamaense, P. hechiense, P. lepidotipinnatum, P. multifolium, and P. paoliense. All six species are so far known only from a single population and five of them each are from a single cave and one from limestone forest. Five species are classified as Critically Endangered (CR), and one as Data Deficient (DD) following IUCN Red List criteria.